Ventricular Septal Rupture Complicating Acute Myocardial Infarction in a Tertiary Care Hospital of Nepal - Laxman Dubey; Ridhi Adhikari; Sogunuru Guruprasad; Gangapatnam Subramanyam (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
Background: Ventricular septal rupture is a rare but fatal mechanical complication of acute myocardial infarction. Although the incidence has decreased, the mortality rate from ventricular septal rupture has remained extremely high. Objectives: The aim of this study was to assess the patient with acute myocardial infarction complicating with ventricular septal rupture and to identify the risk factors for ventricular septal rupture in a tertiary level hospital of Nepal. Patients and Methods: This is a retrospective analysis of 11 patients who were diagnosed as ventricular septal rupture complicating acute myocardial infarction in College of Medical Sciences & Teaching Hospital, Bharatpur, Nepal. Results: All (100%) patients were female with mean age of 65.8±9.3 years. Three patients (27.3%) were smokers, seven (63.6%) were hypertensive, and four (36.4%) were diabetic. None of our patients had previous history of coronary artery disease. Nine (81.8%) patients had ventricular septal rupture in apical septum and two (18.2%) in basal septum. Since there was no backup cardiac surgery facility available in our hospital, all patients were managed conservatively. In-hospital mortality was 90.9%. Conclusions: Ventricular septal rupture following acute myocardial infarction has very high in hospital mortality and is more common in female patients with no previous history of coronary artery disease. Rupture in apical septum is more common than basal septum rupture.